Colchicine in Recently Hospitalized Patients with COVID-19: A Randomized Controlled Trial (COL-COVID) - Pascual-Figal DA; Roura-Piloto AE; Moral-Escudero E; Bernal E; Albendín-Iglesias H; Pérez-Martínez MT; Noguera-Velasco JA; Cebreiros-López I; Hernández-Vicente; Vázquez-Andrés D; Sánchez-Pérez C; Khan A; et al. (International Journal of General Medicine, 2021)
Domingo A Pascual-Figal,1– 3 Aychel E Roura-Piloto,4 Encarnación Moral-Escudero,4 Enrique Bernal,5 Helena Albendín-Iglesias,4 M Teresa Pérez-Martínez,1 Jose Antonio Noguera-Velasco,6 Iria Cebreiros-López,6 Álvaro Hernández-Vicente,1 David Vázquez-Andrés,1 Carmen Sánchez-Pérez,2 Amjad Khan,7 Fátima Sánchez-Cabo,3 Elisa García-Vázquez4 On behalf of the COL-COVID Investigators1Cardiology Department, Hospital Universitario Virgen de la Arrixaca, IMIB-Arrixaca, Universidad de Murcia, Murcia, Spain; 2Centro de Investigación Biomédica en Red Enfermedades Cardiovasculares, (CIBERCV), Madrid, Spain; 3Centro Nacional de Investigaciones Cardiovasculares (CNIC), Madrid, Spain; 4Infectious Diseases and Internal Medicine Department, Hospital Universitario Virgen de la Arrixaca, IMIB-Arrixaca, Universidad de Murcia, Murcia, Spain; 5Infectious Diseases and Internal Medicine Department, Hospital Universitario Reina Sofia, IMIB-Arrixaca, Universidad de Murcia, Murcia, Spain; 6Clinical Biochemistry Department, Hospital Universitario Virgen de la Arrixaca, IMIB-Arrixaca, Universidad de Murcia, Murcia, Spain; 7Department of Chemistry, University of Oxford, Oxford, UKCorrespondence: Domingo A Pascual-FigalLAIB, Despacho 2.52, Av. Buenavista s/n, Murcia, 30120, SpainTel +34-868888163Email dpascual@um.esBackground: Colchicine has been proposed as a potential therapy in coronavirus disease 2019 (COVID-19) due to their anti-inflammatory actions.Methods: The COL-COVID study was a prospective, randomized, controlled and open-label clinical trial that compared colchicine added to standard treatment vs standard treatment in hospitalized COVID-19 patients that do not need mechanical ventilatory support. Colchicine was initiated within the first 48 hours of admission at a 1.5 mg loading dose, followed by 0.5 mg b.i.d. for one week and 0.5 mg per day for 28 days. The study endpoints were clinical status (7-points WHO ordinal scale) and inflammatory biomarkers (IL-6 and CRP).Results: A total of 103 patients (51± 12 years, 52% male) were randomly allocated to colchicine arm (n=52) and control arm (n=51). At day 28, all patients in the colchicine group were alive and discharged, whereas in the control group, two patients died in-hospital and one patient remained hospitalized. Clinical improvement in terms of changes on WHO scale at day 14 and 28 and time to 1-point clinical improvement did not differ between the two groups. Clinical deterioration (increase of at least 1-point in WHO scale) was observed in a higher proportion of cases in colchicine group (13.8%) vs control group (5.8%) (p=0.303); after adjustment by baseline risk factors and concomitant therapies, colchicine therapy was associated with a lower risk of clinical deterioration (p=0.030). Inflammatory biomarkers CRP and IL-6 concentrations course did not differ between the two arms.Conclusion: In hospitalized COVID-19 patients, colchicine treatment neither improved the clinical status, nor the inflammatory response, over the standard treatment. Nevertheless, a preventive effect for further clinical deterioration might be possible.Trial Registration: NCT04350320.Keywords: colchicine, COVID-19, inflammation